Decision Support System Penentuan Jurusan Siswa Baru SMA Menggunakan Metode Simple Additive Weighting - Khilda Afriyani; Abdul Rohman (Universitas Ngudi Waluyo, 2022)
There is a change in the curriculum as well as the increasing number of students from year to year, many criteria are used in determining student majors according to the interests of students talent and desires. With these constraints it will affect the calculations process, so that the results obtained later do not rule out the possibility of non-objective selection. Therefore, the process of majoring in sma negeri 1ungaran which is still done manually need to switch digitization, namely by making a Decision Support System which will later be more effective, efficient and determined according to exixting criteria. This research was designed and developed using the PHP and MYSQL programming languages as the database and using the Simple Additive Weighting (SAW) method to perform weighted summation calculations containing ceveral criteria. From the results of testing using blackbox shows that this program can work according to its function, namely being able to input data and perform calculations for determining student majors. As well as accuracy testing which produces a fairly good level of accuracy of 80% from 100%. From the results of this study, it can be concluded that this system can determine students majors according to their academic interests and talents. And provide effectiveness and efficiency of teachers in helping majors.